VERTICAL TYPE SENSOR - Zan Hsiao-Wen; Meng Hsin-Fei; Dai Ming-Zhi; Chao Yu-Chiang (My University, 2012)
The present invention provides a vertical type sensor, including a substrate; a first electrode formed on the substrate; a sensing layer formed on the first electrode layer and reactive to a target substance, wherein the first electrode layer is interposed between the substrate and the sensing layer; and a second electrode layer formed on the sensing layer and having a plurality of openings, wherein the sensing layer is interposed between the first electrode layer and the second electrode layer, and the target substance contacts the sensing layer via the plurality of openings. The vertical type sensor of the present invention provides instant, sensitive and rapid detection.